Begrafenis van Troelstra in Den Haag. Plaats van personen aangegeven op achterzijde. Vergelijk ook BG B4/194
Begrafenis van Troelstra in Den Haag. Plaats van personen aangegeven op achterzijde. Vergelijk ook BG B4/194.